Comparative Study of Mechanical Properties of MWCNTS/ Epoxy and SWCNTS/ Epoxy Composites (Journal of University of Babylon for Engineering Sciences, 2018)
The single – walled carbon nanotubes (SWCNTs) and multi – walled carbon nanotubes (MWCNTs) embedded into resin matrix with different weight concentrations ranging about (0.1, 0.3, 0.5 and 1 wt. %), the nanocomposites are synthesized by casting method. The main applications of this nanocomposites are in the sensors, actuators, radar. Mechanical tests were done for this study such as: tensile test, bending test and hardness test. Also many examinations were utilized to define the microstructure like scanning electron microscopy (SEM), X-ray diffraction and Raman spectroscopy. The results of this work showed that obviously an improvement in mechanical properties of the processed nanocomposites such as young’s modulus, ultimate tensile strength, bending strength and Shore hardness. Also the micrographs of SEM demonstrated that SWCNTs and MWCNTs homogeneously dispersed into epoxy. On the other hand Raman spectra and XRD revealed that same results for SEM. Finally all the results for mechanical properties and microstructure evaluation show that SWCNTs give extremely higher values and properties than MWCNTs.